Multi-disciplinary north-south collaboration in participatory action research on food value chains: A German-Tanzanian case study on perceptions, experiences and challenges - Graef, F.; Mutabazi, K. D.; Sieber, S.; Asch, F.; Makoko, B.; Nkonya, Ephraim M. (Springer, 2019)
Upgrading local food value chains is a promising approach to invigorating African food systems. This endeavour warrants multi-disciplinary North-South collaboration and partnerships through participatory action research (PAR) to help leverage appropriate upgrading strategies (UPSs) with a focus on local stakeholders. The more disciplines, cultures, and partner institutions that are involved, the more a project will present challenges in terms of communication and coordinating activities. Our aim was to determine the costs and investigate whether PAR with a multi-disciplinary approach was feasible in rural Tanzania with over 600 local stakeholders and more than 100 scientists. This article presents a self-evaluation of the collaboration and communication of project scientists during their research activities. Despite the overall high satisfaction, the more complex and complicated PAR activities required more cooperation, instructions and communication among the project scientists than had been anticipated in this multi-disciplinary, multi-cultural, and multi–institutional context, resulting in greater tension and dissatisfaction. The findings indicate that this type of large multi-disciplinary PAR is challenging in terms of flexibility in the planning of research activities, the administration of finances, and cross-cultural communication. Potential avenues to overcome these obstacles include a) more communication on PAR activities across cultures to develop a shared vocabulary; b) developing other modes of shared responsibility for a more horizontal collaboration; and c) more face-to-face cross-cultural activities to overcome cultural, disciplinary and geographical distance.